Health Equity and Financial Protection : Streamlined Analysis with ADePT Software - Wagstaff, Adam; Bilger, Marcel; Sajaia, Zurab; Lokshin, Michael (World Bank, 2012)
This book provides a guide to Automated Development Economics (DEC) Poverty Tables (ADePT's) two health modules: the first module covers inequality and equity in health, health care utilization, and subsidy incidence; the second, health financing and financial protection. It also provides introductions to the methods used by ADePT and a step-by-step guide to their implementation in the program. ADePT is a software package that generates standardized tables and charts summarizing the results of distributional analyses of household survey data. ADePT health is just one of several modules; other modules include poverty, inequality, labor, social protection, and gender. ADePT health has two sub modules: health outcomes and health financing. Together these modules cover a wealth of topics in the areas of health equity and financial protection. This manual is divided into two parts corresponding to each of these sub modules. The following topics are covered: part 1, health outcomes: (a) measuring inequalities in outcomes and utilization (with and without standardization for need), (b) decomposing the causes of health sector inequalities, and (c) analyzing the incidence of government spending (that is, benefit incidence analysis); and part 2, health financing: (a) financial protection, including catastrophic payments and impoverishing payments, and (b) the progressivity and redistributive effect of health financing.